Positioning Professional Services: Segmenting the Financial Services Market - McAlexander,Jim; Schouten ,John; Scammon ,Debra (Journal of Professional Services Marketing, 1991)
Market segmentation and positioning allow marketers to differentiate themselves from competitors in a manner that is valued by customers and results in competitive advantage. Through an analysis of the financial services market this study develops a segmentation and positioning strategy based on the proposition that consumers employ many kinds of professional service providers to compensate for their own inability or unwillingness to perform certain tasks. Groups of similarly classified informants were examined to create profiles of four distinct market segments with unique needs, expectations, and evaluative criteria.
Keywords: Marketing